2016
DOI: 10.1016/j.acvd.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of systemic right ventricle by echocardiography

Abstract: Improvements in cardiac imaging have recently focused a great interest on the right ventricle (RV). In patients with congenital heart disease, the right ventricle (RV) may support the systemic circulation (systemic RV). There are 2 different anatomic conditions providing such physiology: the congenitally corrected transposition of the great arteries (ccTGA) and the TGA surgically corrected by atrial switch. During the last decades, evidence is accumulating that progressive systemic RV failure develops leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
1
31
1
2
Order By: Relevance
“…In addition to volumetric function parameters, the analysis of longitudinal function parameters has been proposed [1]. In agreement with previous studies, the current study showed no correlation between longitudinal function parameters and sysRV EF.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to volumetric function parameters, the analysis of longitudinal function parameters has been proposed [1]. In agreement with previous studies, the current study showed no correlation between longitudinal function parameters and sysRV EF.…”
Section: Discussionsupporting
confidence: 90%
“…The right ventricle (RV) serves as the subaortic systemic ventricle in patients with congenitally corrected transposition of the great arteries (ccTGA) and in patients with transposition of the great arteries (TGA) surgically repaired by atrial switch. TGA occurs in 1:3100 live births and ccTGA in 1:33,000 live births [1]. Surgical methods for the repair of TGA by performing an atrial baffle repair were developed by Senning and Mustard in the 1950s and 1960s, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…35 Já valores de strain longitudinal de VD inferiores a -10% foram associados à ocorrência de eventos adversos, em PO tardio de cirurgia de Senning. 39 A seleção de pacientes com ventrículo único (VU) para cirurgia de Fontan leva em consideração a resistência vascular pulmonar e a pressão diastólica final ventricular. No entanto, os critérios atuais de indicação mostram-se falhos para uma considerável parcela destes pacientes, que enfrentam complicações e internações prolongadas.…”
Section: Strain Ventricular Em Cardiopatias Congênitasunclassified
“…In Eisenmenger´s syndrome, the development of myocardial fibrosis is closely related to the generation less strength, symptoms such as fatigue or palpitations are attributed to the CHD itself, and the real new HF signs and symptoms are masked by the underlying CHD. A more objective assessment with diagnostic studies such as oxygen consumption during a stress test, 3D echocardiography (Figure 4) or functional MR, which measure the ejection fraction more precisely, is a more adequate and recommended method for measuring ACHDs´ functional capacity [22][23][24][25].…”
Section: What Are the Main Causes Of Decompensation In Adults With Comentioning
confidence: 99%